PEMBERDAYAAN KELUARGA DALAM MENGATASI MASALAH BALITA SAAT BANJIR DI DAYEUHKOLOT KABUPATEN BANDUNG: PEMBERDAYAAN KELUARGA DALAM MENGATASI MASALAH BALITA SAAT BANJIR DI DAYEUHKOLOT KABUPATEN BANDUNG - Supriadi, Supriadi; Fathudin, Yogasliana (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2025)
In Indonesia, especially in West Java Province, floods are the most frequent disaster, especially during the rainy season. Children under five are especially vulnerable to health problems in flooded areas, including the risk of drowning. Therefore, the family as the closest party needs to provide first aid to reduce the direct and indirect impacts of flooding. This community service activity aims to increase the knowledge and skills of cadres and families in dealing with toddler problems during floods. The method used is training for cadres and assistance for families regarding handling toddler problems during floods. This activity was aimed at 14 cadres and 28 families with toddlers, located in Citeureup Village, Dayeuhkolot District, Bandung Regency. The results of the activity showed an increase in the average knowledge and skills of cadres in handling drowning in toddlers from 48.2 to 87.2, as well as an increase in family understanding regarding emergency management of drowning from 35,2 to 68,5. It is important for cadres and families to disseminate knowledge and skills regarding handling emergency for drowning children as first aid before being taken to a health facility. Apart from that, related agencies are expected to be able to optimize the Disaster Management Team by empowering families and young people of youth groups in handling emergencies due to flooding. Keywords: Empowerment, Cadre, Family, Toddlers, Flood